A Case of Proceeding Polycystic Kidney Progress to the End Stage Renal Failure - Khayati Moudgil (Journal of Global Pharma Technology, 2019)
Polycystic Kidney Disease (PKD) commonly an inherited monogenic disease, associated with severe morbidity and mortality. It is categorized by renal cyst formation and renal enlargement. Autosomal dominant polycystic kidney (ADPKD) causes end stage kidney disease and is most commonly seen in adults. Worldwide overall incidence is 1-2% and mutations in both the genes PKD1 and PKD2 causes ADPKD. Most of the ADPKD patients shows decline in renal function where as 70% leads to end- stage renal disease. An alarming non-communicable disease conditions currently with no cure causing a major public health concern as well as the economic burden on healthcare system. Here with we report a case of preceding polycystic kidney progress to the end stage renal failure, along with our understanding towards the management involved in the disease.Keywords: Polycystic Kidney Disease, Autosomal Dominant Polycystic Kidney Disease, End Stage Renal Failure, Hypertension.